Disseminated peritoneal lieomyomatosis after 10 years post TAHBSO: a case report - Tehrani, Seyed Jalaledin Tahsildar; Thean, Yean Kew; Mohd Amir Mohd Amir Kamaruzzaman (Penerbit Universiti Kebangsaan Malaysia, 2020)
Disseminated peritoneal leiomyomatosis (DPL) is a rare condition characterized by the development of multiple smooth muscle-like nodules in extra-uterine region specifically in the peritoneal cavity. We introduce a case of DPL in a 50 year-old-female who presented with symptoms of abdominal pain suspicious for bowel obstruction. With the previous history of total abdominal hysterectomy and bilateral salpingo-oophorectomy (TAHBSO) since 10 years ago, bowel obstruction due to adhesion was the first provisional diagnosis. The following CT imaging of the abdomen showed a mass within the pelvis with subsequent laparotomy and evacuation of the mass. Biopsy and histopathology result showed leiomyoma. Second episode of bowel symptoms appeared one year later with abdomino-pelvic CT imaging demonstrated the recurrence of the mass at the same location within the pelvis and she was proceeded with removal of mass with similar histopathological result. While the growth of leiomyoma is mainly dependent on oestrogen hormones, absence of the ovaries as the main source of oestrogen in our case, makes it less likely to become a differential diagnosis. So far, few cases of DPL have been reported in post menopause women. This case report may bring clinical implication in term of guideline management of DPL. A careful history taking and thorough investigation with multidisciplinary experts involvement become a crucial aspect for DPL to be suspected so that the appropriate management, surgical intervention, subsequent follow up and surveillance can be achieved to improve patient outcome.